Impedance measurement techniques for DC-biased systems - Henriksson (My University, 2025)
Abstract This thesis compiles information about six methods for impedance measurement of DC biased systems. It describes a physical interface for low-voltage Devices Under Test (DUTs) using the shunt-through method with DC-blocking capacitors. The interface is used to measure impedance versus frequency of three pouch cells of different dimensions and chemistries. In addition to the cell measurements, a separate set of measurements are carried out on inductors and capacitors with and without the use of the DC-blocking interface. The measurements show how parameters such as heat, conductor length and measurement setup affect the measured impedance. An interface model is presented that explains in what frequency and DUT impedance ranges each parasitic interface parameter affects the measurement results, and in what way. The conclusion of the thesis is that the used capacitor-based impedance measurement method was not accurate when measuring the low impedance of an electric vehicle battery cell. However, with the modification and improvements outlined in the thesis, the interface type could be used to measure devices with larger impedance, such as a complete high voltage electric vehicle battery consisting of the same cells.
Keywords: Keywords: EMC, Batteries, impedance, EIS, Impedance Spectroscopy, Power Electronics.